(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Hypertension is a disease often encountered in the elderly. This occurs due to physiological and lifestyle changes including eating habits. Food consumption habits of high cholesterol sources can result in the accumulate of fat in blood vessels and forming plaque. It result in an increase in blood pressure that leads to hypertension. The purpose of this research is to analyze the correlation of food consumption habits saturated fat sources with hypertension in elderly woman. This study uses case control design with sample of elderly female in Health Centre Gunung Anyar Surabaya. Subject consisting of 28 cases and 28 controls. Data food consumption of saturated fat obtain through recall method Semi Quantitative Food Frequency Questionnare (SQ-FFQ). Blood pressure is measured using sphygnomanometer. The statistical test performed is the chi square test. The result showed that there was a significant relationship between food consumption saturated fat acid sources with hypertension among elderly woman (p = 0,01). The conclusion of this study is that there is a significant relationship between the food consumption of saturated fat acid with hypertension in elderly women.